Characteristics of patients with rheumatoid arthritis in France: a study of 1109 patients managed by hospital based rheumatologists. Issue 10 (10th September 2004) - Sany, J; Bourgeois, P; Saraux, A; Durieux, S; Lafuma, A; Daurès, J P; Guillemin, F; Sibilia, J
Abstract : Objective: To describe the characteristics of rheumatoid arthritis in patients managed by hospital based rheumatologists in France. Methods: All public and non-profit private hospitals in France were invited to participate in a cross sectional study. Clinical data on the day of inclusion and health resources used for rheumatoid arthritis over the previous 12 months (treatments, medical devices, physician visits, examinations, hospital admissions, and other health professional care) were recorded. Results: 1109 patients from 75 centres located throughout the country were included (846 female; mean disease duration, 10.6 years; mean age, 56.7 years). Active disease (swollen joint count ⩾6, tender joint count ⩾6, and two of: morning stiffness ⩾45 min, C reactive protein ⩾20 mg/l, erythrocyte sedimentation rate >28 mm/h) was observed in 146 patients (13.2%). Mean (SD) DAS28 was 4.51 (1.55). Severe extra-articular manifestations were reported in 8.4%. ACR functional status was: class I, 19%; class II, 28%; class III, 31%; class IV, 22%. Comorbidity was observed in 44.9% of cases, particularly chronic pulmonary disease and coronary or peripheral vascular disease. Average AIMS2-SF dimension scores were between 4.56 and 6.18, and mean HAQ was 1.32 (0.77). Disease modifying antirheumatic drugs (DMARDs) were prescribed for 82.1% of the patients. During the previous four weeks, one DMARD was used in 62.5%, and two or more in 19.5%. Corticosteroids were prescribed in 72%. Conclusions: In a rheumatoid arthritis population managed by hospital based rheumatologists, the disease was active in 13% and severe in more than one third of cases.